2019
DOI: 10.1097/aog.0000000000003167
|View full text |Cite
|
Sign up to set email alerts
|

A Nudge Toward Universal Aspirin for Preeclampsia Prevention

Abstract: The July 2018 American College of Obstetricians and Gynecologists' guidelines for aspirin prophylaxis for preeclampsia prevention represent a departure from prior, more stringent guidelines and extend eligibility for aspirin prophylaxis to a large proportion of pregnant women in the United States. However, these latest guidelines are predicated on a complex, risk-factor–based screening algorithm and ignore the reality that, outside of the setting of clinical research, effective implementation of risk-factor–ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…A recent expert commentary highlighted the historically poor rate of provider follow through with risk-based screening. 8 Research should not end with positive randomized trials demonstrating clinical benefit. Our study underscores the importance of evaluating the implementation of evidencebased guidelines to ensure patients are actually benefiting from the research conducted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent expert commentary highlighted the historically poor rate of provider follow through with risk-based screening. 8 Research should not end with positive randomized trials demonstrating clinical benefit. Our study underscores the importance of evaluating the implementation of evidencebased guidelines to ensure patients are actually benefiting from the research conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, study of implementation of guidelines has identified a significant percentage of providers who do not adhere to recommended practices. 6,8 Specifically in OBs, studies have evaluated risk-based screening for gestational diabetes, 11 utilization of progesterone for preterm birth prevention, [12][13][14] and cervical length screening. [15][16][17] These studies have prompted a change in clinical practice to improve adherence (i.e., opt out instead of opt in, as with cervical length screening), 15,18 and removing barriers to progesterone access.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Ayala et al also reported that moving from an "opt-in" to an "opt-out" system greatly increased the rate of providing aspirin prophylaxis for preeclampsia prevention. 22 Automated dashboard with active choice and peer comparison performance feedback to physicians had increased statin prescribing for primary care physicians. 23 In our institute, several feasible and low-cost strategies were applied.…”
Section: Discussionmentioning
confidence: 99%
“…Although this information would be interesting to evaluate we do not think it biases our results as its likely greatest impact would be on reducing our primary outcomes in women with stage 2 hypertension and dampening the increased risk between women with stage 1 and stage 2 hypertension. 9,[17][18][19][20] Finally, almost half of the deliveries that occurred during the study time frame were excluded due to the lack of prenatal records for blood pressure categorization which may have introduced selection bias.…”
Section: Strengths and Limitationsmentioning
confidence: 99%